Bringing corporate governance into internalization theory: State ownership and foreign entry strategies - Grøgaard, Birgitte; Rygh, Asmund; Benito, Gabriel R. G. (Journal of International Business Studies, 2019)
We use internalization theory to analyze the establishment and entry mode decisions of state-owned (SOE) and privately owned (POE) enterprises. We enrich internalization theory by building on insights from economic theory of corporate governance and taking into account particular characteristics of SOEs such as non-economic motivations, long-term orientation, and different risk preferences. We examine foreign entries over a 10-year period in the Canadian oil and gas industry. This single-country and single-industry context features foreign SOEs and POEs from a wide range of home countries, allowing a focused study of the combined influence of state ownership and home-country factors. Compared to POEs, SOEs tend to prefer acquiring stand-alone assets rather than firms, and to take lower ownership shares. We also find that differences between SOEs and POEs diminish when home countries are characterized by high government quality and market orientation and identify differences between types of SOEs, with partially owned SOEs exhibiting behaviors more similar to POEs than fully owned SOEs. We demonstrate how our enrichment of internalization theory strengthens its predictive and explanatory capacity. Our results also show that SOEs from strong and market-oriented institutional environments are similar to POEs and can be studied using the traditional internalization theory.